Role of neurorehabilitative treatment using transcranial magnetic stimulation in disorders of consciousness - Formica, Caterina (J Int Med Res, 2021)
Disorders of consciousness (DOC) result from brain injuries that cause functional changes in vigilance, awareness and behaviour. It is important to correctly diagnose DOC so that the most appropriate rehabilitation treatments can be initiated. Several studies in DOC patients have demonstrated that repetitive transcranial magnetic stimulation (rTMS) has an important role to play in the recovery of consciousness as highlighted by monitoring clinical scale scores. Although studies indicate that rTMS can be used to aid recovery, it is not combined with other rehabilitative cognitive treatments. As of December 2018, there have been no studies published that combined DOC cognitive rehabilitation with TMS. This current review describes the use of rTMS as a form of non-invasive brain stimulation, as distinct from its use as a tool to investigate residual cortical activity, in terms of its possible therapeutic effects including cognitive rehabilitation. Literature searches were undertaken to identify all relevant studies. The available evidence suggests that rTMS may have an important role to play in in monitoring brain function during recovery and making other intensive rehabilitation treatments more effective, such as sensorial stimulations and cognitive training in patients after a severe acquired brain injury. Further research is required to establish the usefulness of rTMS treatment in DOC rehabilitation.